Process, Project and Architecture - Paolo De Marco; Antonino Margagliotta; Fran Silvestre (Agathón)
The concept of systematization is an innovative approach to the project that introduces a system of order with a method that proceeds by aggregating repeatable parts and regulates the phases of the design process. These principles can be found in the theories and experiments that lead to contemporary architecture, such as seriality, standardization, modularity that transform the project into a process and determine a new aesthetic. The works of the Fran Silvestre Arquitectos studio represent interesting examples that highlight the clarity of the process that operates through seriality and the definition of configurations based on dimensional relationships rather than on scale factors (as inherent in the concept of type) from which coherent structural and spatial solutions derive.